Ineffective CD8(+) T-Cell Immunity to Adeno-Associated Virus Can Result in Prolonged Liver Injury and Fibrogenesis - Spahn, Jessica (American Society for Investigative Pathology, 2011)
Chronic viral hepatitis depends on the inability of the T-cell immune response to eradicate antigen. This results in a sustained immune response accompanied by tissue injury and fibrogenesis. We have created a mouse model that reproduces these effects, based on the response of CD8(+) T cells to hepatocellular antigen delivered by an adeno-associated virus (AAV) vector. Ten thousand antigen-specific CD8(+) T cells undergo slow expansion in the liver and can precipitate a subacute inflammatory hepatitis with stellate cell activation and fibrosis. Over time, antigen-specific CD8(+) T cells show signs of exhaustion, including high expression of PD-1, and eventually both inflammation and fibrosis resolve. This model allows the investigation of both chronic liver immunopathology and its resolution.